Species differences between rat and human in vitro metabolite profile, in vivo predicted clearance, CYP450 inhibition and CYP450 isoforms that metabolize benzanthrone: Implications in risk assessment. (January 2018) - Taneja, Isha; Karsauliya, Kajal; Rashid, Mamunur; Sonkar, Ashish Kumar; Rama Raju, Kanumuri Siva; Singh, Sandeep Kumar; Das, Mukul; Wahajuddin, Muhammad; Singh, Sheelendra Pratap
Abstract: Benzanthrone (BNZ) is a polycyclic aromatic hydrocarbon found in industrial effluent causing skin, respiratory, gastrointestinal, genitourinary, nervous and hemopoietic toxicity. While its toxicity has been well studied, its metabolism in humans has not been investigated. The aim of this study was to characterize species differences in the in vitro metabolism of BNZ in rat and human liver microsomes and to identify the CYP isoforms involved in its metabolism. Upon incubation in liver microsomes, BNZ was found to be a direct substrate of phase I metabolism in both rat and human, undergoing oxidation and reduction. The Km in rat, 11.62 ± 1.49 μM, was two-fold higher than humans (5.97 ± 0.83 μM) suggesting higher affinity for human CYPs. Further, incubation with human rCYPs, BNZ was found to be substrate of multiple CYPs. The predicted in vivo hepatic clearance was 63.55 and 18.91 mL/min/kg in rat and human, respectively, indicating BNZ to be a high clearance compound. BNZ was found to be a moderate inhibitor of human CYP1A2. BNZ metabolism by multiple CYPs indicates that single enzyme genetic polymorphism is unlikely to have profound effect on the toxicokinetics of BNZ and default uncertainty factor of 3.16 might be sufficient to capture the intraspecies kinetic variability. Graphical abstract: Highlights: Species difference in BNZ metabolism is investigated. BNZ was metabolized by multiple CYP450 isoform. BNZ showed high Clearance and same metabolites profile in rat and human. BNZ showed moderate inhibition of human CYP1A2.